1991
DOI: 10.3186/jjphytopath.57.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weakly-virulent bacteriocin-producing strain of Pseudomonas solanacearum on the protection of tobacco plant from bacterial wilt.

Abstract: Two mutant strains of bacteriocin-producing Pseudomonas solanacearum, both of which derived from a virulent bacteriocin-producing strain Ps48, protected tobacco plants from bacterial wilt, when the root systems of tobacco seedlings were dipped in each suspension prior to transplanting in soil infested with virulent strain Ps29. Among them tobacco plant treated with weakly virulent bacteriocin-producing strain (OM2) gave better control than that treated with avirulent bacteriocin-producing strain (OM1). Tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Several researchers have reported successful control of bacterial wilt using avirulent or weakly virulent strains derived from virulent strains due to the suppression of root colonization (McLaughlin and Sequeira 1988;Trigalet and Trigalet-Demery 1990;Hara and Ono 1991). Again, this study confirmed that the R. solanacearum strains were effective antagonists for the suppression of root colonization by the bacterial wilt pathogen.…”
Section: Discussionsupporting
confidence: 78%
“…Several researchers have reported successful control of bacterial wilt using avirulent or weakly virulent strains derived from virulent strains due to the suppression of root colonization (McLaughlin and Sequeira 1988;Trigalet and Trigalet-Demery 1990;Hara and Ono 1991). Again, this study confirmed that the R. solanacearum strains were effective antagonists for the suppression of root colonization by the bacterial wilt pathogen.…”
Section: Discussionsupporting
confidence: 78%
“…Several biocontrol studies that use nonpathogenic mutants as the biocontrol agent have aimed at utilizing the production of bacteriocin as a mechanism for enhancing the biological control (26,46). In the case of B. solanacearum, this approach has met with limited success (3,21,44). However, recent studies indicate that spontaneous nonpathogenic mutants of B. solanacearum which are impaired in exopolysaccharide production are unable to colonize the host plant (42,45) and consequently exhibit poor biocontrol ability (41).…”
mentioning
confidence: 99%
“…Several strategies have been developed to control this disease including biological control by introducing biocontrol agent1,4, 8,10,25,27) It was reported that some strains of P. fluorescens actively suppress the disease occurrence of BWT when they were introduced to plant rhizosphere by root dipping. From our preliminary study we found that some of these strains produce both antibi- were chosen as the representative strains of antibiotics non-producing mutant and of siderophore non-producing one, respectively.…”
Section: Introductionmentioning
confidence: 99%